2017
DOI: 10.3832/ifor2101-010
|View full text |Cite
|
Sign up to set email alerts
|

Use of alternative containers for promoting deep rooting of native forest species used for dryland restoration: the case of Acacia caven

Abstract: The size of a container determines the development and quality of root systems. In the case of taprooted forest species used for dryland reforestation, deeper containers may favour early root development and, consequently, better soil profile colonization after outplanting. Although research on container design for worldwide tree species has been developed in the last decades, technical solutions for containerized forest species with a taproot system have been poorly documented. We present a case study using A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…The effect of increasing container volume on seedling morphology development is widely documented (Prieto-Ruiz et al 2007, Gil & Díaz 2016. However, the effect of increased container depth on seedling morphology may have different responses according to species characteristics (Chirino et al 2005, Kostopoulou et al 2011, De la Fuente et al 2017. In this study, a deep container was used to produce seedlings with a longer taproot and a higher DWR/ DWS ratio to favour not only deep root system development, but also the rapid colonization of deeper soil layers before the first summer.…”
Section: Effect Of Deep Container On the Morphological Characteristicmentioning
confidence: 97%
See 2 more Smart Citations
“…The effect of increasing container volume on seedling morphology development is widely documented (Prieto-Ruiz et al 2007, Gil & Díaz 2016. However, the effect of increased container depth on seedling morphology may have different responses according to species characteristics (Chirino et al 2005, Kostopoulou et al 2011, De la Fuente et al 2017. In this study, a deep container was used to produce seedlings with a longer taproot and a higher DWR/ DWS ratio to favour not only deep root system development, but also the rapid colonization of deeper soil layers before the first summer.…”
Section: Effect Of Deep Container On the Morphological Characteristicmentioning
confidence: 97%
“…Previous studies that employed containers with similar depths in Quercus coccifera, Q. ilex (Chirino et al 2005) and Q. suber (Chirino et al 2008) reported the production of seedlings with no significant differences in height and basal diameter compared to those grown in standard containers. This also allowed to produce seedlings destined to dry ecosystems with a higher DWR/DWS ratio in the seedlings grown in deep containers (Chirino et al 2005, 2008, Mariotti et al 2015b, which favours better root growth and greater resistance to Mediterranean water stress characteristics (Pemán et al 2006, De la Fuente et al 2017. Other studies that have employed deep containers produced seedlings with a longer taproot (Trinidad et al 2015) and a higher stem height (Mariotti et al 2015c).…”
Section: Effect Of Deep Container On the Morphological Characteristicmentioning
confidence: 99%
See 1 more Smart Citation
“…Various ecotechnological treatments could help to dampen or reduce competition with Stipa and tilt the net balance of the grass-shrub interaction toward a neutral or positive interaction. For example, techniques that promote niche differentiation between shrubs and grasses, such as the use of long containers for seedling production to promote deeper rooting (de la Fuente et al, 2017), combined with deep planting (Oliet et al, 2012) and/or deep preparation of the soil for planting (Chirino et al, 2009), can help to overcome the initial overlap of rooting depths earlier, accelerating one of the effects of the natural ontogeny process on slow-growing tall shrubs.…”
Section: Applications To Restorationmentioning
confidence: 99%
“…Other studies conducted in arid, semi-arid, and dry tropical areas have proven the positive effect between root length and seedling survival after transplanting (Markesteijn and Poorter, 2009;León et al, 2011;Ovalle et al, 2015). De La Fuente et al (2017) pointed out that a seedling with a long taproot has adequate morphology and biomass distribution allowing it to colonize deep soil layers. These characteristics thus improve the physiological response of seedlings to water stress conditions (Chirino et al, 2008).…”
Section: Introductionmentioning
confidence: 97%